Squeeze Cementing Using Braden Head Squeeze Method On ‘Dsr-29’ Well Tarakan Field PT. Medco E&P Indonesia - Ristiyan Ragil Putradianto; Dafa Surya Ramadhan (Journal of Petroleum and Geothermal Technology, 2020)
Squeeze cementing is an operation in which a cement slurry is pressed to a certain pressure on an oil or gas well. The purpose of doing squeeze cementing is to block water or gas flow and oil zones, close certain zones to produce other productive zones, repair damaged casing, and as a continuation of primary cementing work. Squeeze Cementing is done when workover a well. Workover and well service operations in a well, is a type of activity in the oil industry aimed to maintain wells so that they can continue to produce optimally and increase productivity back wells due to production problems. Squeeze Cementing Project on Tarakan field, DSR-29 well serves to block perforation that is no longer needed or open hole section at a depth of 630 - 635 m (670 MZ) so that a reservoir can be isolated and the casing can be firm or strong against pressure. Squeeze cementing method used in the well is the Braden Head Squeeze method. In the middle of workover process, there are problems such as existence of remaining perforating gun, and gas traps. Certain procedure is applied so that the cementing process has been carried out successfully.